Ligusaginoids A–D, four eremophilane-type sesquiterpenoid dimers and trimers from Ligularia sagitta. Issue 38 (19th September 2018) - Li, Hang-Ying; Zheng, Zai-Qin; Wei, Wen-Jun; Chen, Jian-Jun; Gao, Kun
Graphical abstract: Highlights: Isolation of four novel eremophilane-type sesquiterpenoid dimers and trimers from Ligularia sagitta. The absolute configuration of 1 was confirmed by single crystal X-ray data. The plausible biosynthetic pathway of1 –4 was proposed. Abstract: Four novel highly oxygenated eremophilane-type sesquiterpenoid dimers and trimers with the unique 6/6/5/5 polycyclic skeleton, designated as ligusaginoids A–D (1 –4 ), were isolated from the aerial parts of Ligularia sagitta . Their structures with absolute configurations were determined by a combined method. Moreover, a plausible biosynthetic pathway of1 –4 was also proposed. These compounds showed weak antibacterial activities.